Biopolymer modified slurry fractional crystallization water-soluble fertilizer and production method thereof

CN123026469APending Publication Date: 2026-11-03HUBEI EZHONG ECOLOGICAL AGRI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611108170.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing water-soluble fertilizers suffer from poor crystal morphology, are prone to agglomeration, have unstable particle size distribution, uneven distribution of trace elements, and low utilization rate of mother liquor resources.

Method used

The biopolymer modified slurry graded crystallization technology is adopted. By embedding polymer modifiers such as sodium carboxymethyl cellulose and sodium polyaspartate during the crystallization process, combined with a three-stage graded crystallization process, crystal growth and trace element distribution are controlled, so as to achieve precise control of particle size and graded reuse of mother liquor.

Benefits of technology

The prepared water-soluble fertilizer crystals are spherical, with good flowability, narrow particle size distribution, uniform distribution of trace elements, and high utilization rate of mother liquor resources. It reduces the crystal surface of waste, solves the technical problems that have not been effectively solved in the prior art, and achieves efficient crystal morphology improvement and resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123026469A_ABST
    Figure CN123026469A_ABST
Patent Text Reader

Abstract

The application discloses a kind of biological macromolecule modified slurry fractional crystallization water-soluble fertilizer, belongs to water-soluble fertilizer technical field, including the following weight fraction ratio of raw materials: polyphosphate ammonium 30~50 parts, potassium nitrate 20~35 parts, urea 5~15 parts, potassium sulfate 0~10 parts, sodium carboxymethyl cellulose 2~5 parts, polyaspartic acid sodium 1~3 parts, polyvinyl alcohol 0.3~0.8 parts, nano attapulgite 0.5~1.5 parts, zinc sulfate 0.5~2.0 parts, boric acid 0.3~1.0 parts, manganese sulfate 0.3~1.0 parts, ammonium molybdate 0.05~0.2 parts.The application, by introducing sodium carboxymethyl cellulose and polyaspartic acid sodium as modifier in the crystallization process, two kinds of macromolecular chains are embedded in the crystal inside when crystal growth, selectively inhibit the rapid growth of acicular crystal face, make crystal along each axis development tend to be balanced, finally grow into near spherical equiaxed particle;With subsection cooling process let crystal slowly grow under stable condition, appearance is more regular, particle interfacial area is greatly reduced, flowability is obviously improved, not easy to stick together during storage process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water-soluble fertilizer technology, specifically to a biopolymer modified slurry graded crystallization water-soluble fertilizer and its production method. Background Technology

[0002] Water-soluble fertilizers have advantages such as high nutrient content, fast dissolution speed, and high absorption and utilization rate. They are widely used in water and fertilizer integration planting modes such as drip irrigation and sprinkler irrigation. Crystallization method can produce water-soluble fertilizers with high purity and good fluidity. It is an important process route for water-soluble fertilizer production. Compared with traditional intermittent crystallization, continuous crystallization technology has significant advantages such as large production capacity, low energy consumption, and stable product quality.

[0003] Improvements to the continuous crystallization of water-soluble fertilizers have emerged in existing technologies. For example, invention patent CN116549999A discloses a continuous crystallization method for water-soluble fertilizers. This method involves continuously mixing the crystallization stock solution and circulating mother liquor in a mixer. A supersaturation intelligent controller adjusts the flow ratio of the crystallization stock solution and mother liquor, as well as the temperature of the mixed solution, to reduce supersaturation and thus decrease the number of nuclei. Taking calcium nitrate crystallization as an example, this invention uses concentrated calcium nitrate material with a density ≥1.50 g / cm³ mixed with mother liquor at a flow ratio of 4:1. After approximately 30 hours of cooling to below 35°C, calcium nitrate crystals of 0.1~2.0 mm are obtained, with a daily output of 120 tons. This significantly improves production capacity and reduces energy consumption compared to intermittent crystallization.

[0004] However, the aforementioned existing technologies still have the following main drawbacks:

[0005] The core of this scheme is to reduce nucleation by controlling supersaturation and adjust particle size by stirring speed. Essentially, it is still a passive control of the physical conditions of crystallization. It does not involve adding crystallization modifiers or crystal habit regulators to actively change the growth habit and crystal orientation of crystals. The resulting crystals are still mainly based on the crystallization habit of the raw materials themselves. The crystals of common water-soluble fertilizer raw materials such as calcium nitrate, potassium nitrate, and potassium sulfate are mostly needle-shaped or plate-shaped, with poor fluidity and easy agglomeration. This scheme does not add any polymer modifiers (such as sodium carboxymethyl cellulose, sodium polyaspartate, etc.) during the entire crystallization process, and does not utilize polymer chains to embed inside or on the surface of the crystal to change the crystal morphology, improve particle strength or improve surface hydrophobicity. The crystal surface is exposed, resulting in poor fertilizer efficiency. Therefore, a method for producing a biopolymer-modified slurry graded crystallization water-soluble fertilizer is proposed to solve the above problems. Summary of the Invention

[0006] Purpose of the invention To address the shortcomings of existing technologies, this invention provides a biopolymer-modified slurry graded crystallization water-soluble fertilizer and its production method. It has the advantages of precise and controllable particle size in three-stage graded crystallization, uniform distribution of chelated trace elements, and high resource utilization rate of mother liquor through tiered reuse. It solves the problems of poor crystal morphology and easy agglomeration, wide particle size distribution and batch instability, easy hydrolysis and precipitation of trace elements with uneven distribution, and nutrient waste due to single-stage reuse of mother liquor in existing continuous crystallization technologies.

[0007] Technical solution To achieve the goals of precise and controllable particle size control, uniform distribution of chelated trace elements, and high resource utilization rate of mother liquor through tiered reuse, this invention provides the following technical solution: a biopolymer modified slurry graded crystallization water-soluble fertilizer, comprising the following raw materials in the indicated weight ratios: ammonium polyphosphate 30-50 parts, potassium nitrate 20-35 parts, urea 5-15 parts, potassium sulfate 0-10 parts, sodium carboxymethyl cellulose 2-5 parts, sodium polyaspartate 1-3 parts, polyvinyl alcohol 0.3-0.8 parts, nano-attapulgite 0.5-1.5 parts, zinc sulfate 0.5-2.0 parts, boric acid 0.3-1.0 parts, manganese sulfate 0.3-1.0 parts, and ammonium molybdate 0.05-0.2 parts; The fertilizer is a crystalline spherical aggregate with a composite modified layer of sodium carboxymethyl cellulose, sodium polyaspartate and polyvinyl alcohol embedded in the interior and surface of the crystal. Ammonium polyphosphate polymerizes phosphate and trace elements to form a chelate coordination structure.

[0008] Preferably, the sodium carboxymethyl cellulose has a degree of substitution ≥0.9, the sodium polyaspartic acid has a molecular weight of 3000~8000, the polyvinyl alcohol is type 1788 and has a degree of alcoholysis of 88%; the weight ratio of sodium carboxymethyl cellulose, sodium polyaspartic acid and polyvinyl alcohol is 2~3:1:0.3~0.5.

[0009] Preferably, the particle size D90 of the nano-attapulgite is ≤2μm, and the degree of polymerization of the ammonium polyphosphate is 2~10.

[0010] Another technical problem to be solved by the present invention is to provide a method for producing a water-soluble fertilizer made from biopolymer-modified slurry through graded crystallization, comprising the following steps: S1. Pretreatment with biopolymer modifier: Sodium carboxymethyl cellulose, sodium polyaspartate and polyvinyl alcohol are added to a mixing device in a certain proportion and mixed evenly to obtain a composite modifier; nano-attapulgite is crushed separately to D90≤2μm using a crushing device. S2. Preparation of crystallization slurry: Add deionized water to the reactor, heat to 80~95℃, and add ammonium polyphosphate, potassium nitrate, urea and potassium sulfate in sequence, stirring to dissolve and form a supersaturated slurry; S3. Simultaneous dispersion of nucleating agent and trace elements: After dispersing nano-attapulgite with zinc sulfate, manganese sulfate, boric acid and ammonium molybdate, add it to the slurry and stir evenly; S4, High-temperature crystallization: S4.1, First-stage high-temperature crystallization: Cool the slurry to 65~75℃, add the composite modifier from step S1, stir for 20~40 minutes, and fine crystal nuclei will precipitate. S4.2, Secondary medium-temperature crystallization: Cool the slurry to 45~55℃, crystallize at a constant temperature for 60~120min, and grow crystals into spherical aggregates; S4.3, Three-stage low-temperature aging: Cool the slurry to 20~30℃ and age for 120~180min; S5. Staged filtration: After two stages of sieving and filtration, the crystals and mother liquor of each stage are collected separately. S6. Mother liquor reuse: Mother liquor from each stage is returned to the corresponding crystallization stage for recycling. S7. Low-temperature drying: Dry the collected crystals. The drying process is carried out at a temperature of 45~50℃ in the first stage and 30~35℃ in the second stage until the moisture content of the crystals is ≤1.0%. S8. Screening and Packaging: Collect the qualified crystals that have been dried in step S7 and have a size of 0.3~1.5mm, and package them in a moisture-proof manner to obtain the required water-soluble fertilizer.

[0011] Preferably, the weight ratio of sodium carboxymethyl cellulose, sodium polyaspartate, and polyvinyl alcohol in the composite modifier described in step S1 is 2~3:1:0.3~0.5.

[0012] Preferably, the amount of composite modifier added in step S1 is 3% to 6% of the total mass of the solid raw materials, and the nano-attapulgite clay is pulverized by air jet milling to D90 ≤ 2μm. Preferably, the amount of deionized water used in step S2 is 1.0 to 1.5 times the total mass of the solid raw materials, and the pH value of the crystallization slurry does not need to be adjusted in step S4.

[0013] Preferably, in step S3, the dispersion of the nano-attapulgite clay and trace elements is performed by ultrasonic dispersion equipment with ultrasonic vibration dispersion at a frequency of 40kHz, a power of 200W, and a vibration dispersion time of 15~20min.

[0014] Preferably, the mesh sizes of the two-stage sieving and filtration in step S5 are 150 mesh and 325 mesh, respectively. After the two-stage sieving and filtration, crystals with a particle size >0.1 mm are retained as coarse crystal fractions and returned to step S4 as seed crystals; crystals with a particle size of 0.045~0.1 mm are retained as finished crystals and enter the drying process in step S7; crystals with a particle size <0.045 mm are retained as fine crystal fractions and returned to step S4 as seed crystals.

[0015] Preferably, in step S7, the first stage air velocity of the two-stage low-temperature drying is 1.5~2.0m / s, and the second stage air velocity is 1.0~1.5m / s; in step S8, the moisture-proof packaging adopts nitrogen-filled aluminum-plastic composite bag packaging, and the relative humidity of the packaging environment is ≤25%.

[0016] Beneficial effects Compared with the prior art, the present invention provides a biopolymer modified slurry graded crystallization water-soluble fertilizer and its production method, which has the following beneficial effects: 1. The biopolymer modified slurry graded crystallization water-soluble fertilizer and its production method introduce sodium carboxymethyl cellulose and sodium polyaspartate as modifiers during the crystallization process. The two polymer chains are embedded inside the crystal during crystal growth, selectively inhibiting the rapid growth of needle-like crystal faces, making the crystal development along each axis tend to be more balanced, and finally growing into near-spherical equiaxed particles. Combined with a segmented cooling process, the crystal grows slowly under stable conditions, resulting in a more regular morphology, a significant reduction in the contact area between particles, a significant improvement in fluidity, and less tendency to stick together and clump during storage.

[0017] 2. This biopolymer-modified slurry graded crystallization water-soluble fertilizer and its production method employ a three-stage graded crystallization process. Nucleation is induced in a high-temperature stage, crystal growth is promoted in a medium-temperature stage, and aging and homogenization are completed in a low-temperature stage. Combined with the steric hindrance effect of the polymer modifier to inhibit secondary nucleation, the crystals grow along the expected path at each stage. The product has a narrow particle size distribution, good batch-to-batch consistency, and eliminates the need for repeated sieving in subsequent processes, thus improving yield.

[0018] 3. The graded crystallization water-soluble fertilizer and its production method based on the modified biopolymer slurry utilize the natural chelating ability of the carboxyl and amide groups on the sodium polyaspartate molecular chain for metal ions such as zinc and manganese. During the crystallization growth stage, trace elements are locked in a chelated state inside the crystal and precipitated together with the crystal. At the same time, the graded crystallization process provides a sufficient incorporation window for trace elements, ensuring that the trace element content of each particle in the final product is consistent, avoiding the situation where some particles contain trace elements while others do not contain any at all.

[0019] 4. The biopolymer modified slurry graded crystallization water-soluble fertilizer and its production method have different compositions of mother liquor separated at each crystallization stage. After graded collection, they are returned to the corresponding crystallization stage for reuse, avoiding nutrient waste. The modifiers and trace elements remaining in the mother liquor are also reused and continue to participate in the crystallization process. This reduces the amount of fresh modifier to be added, lowers wastewater discharge and treatment costs, and significantly improves the overall raw material utilization rate. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the method flow of the present invention. Detailed Implementation

[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] Example 1: A biopolymer modified slurry graded crystallization water-soluble fertilizer comprises the following raw materials in the indicated weight ratios: 40 parts ammonium polyphosphate, 28 parts potassium nitrate, 10 parts urea, 5 parts potassium sulfate, 3.5 parts sodium carboxymethyl cellulose, 1.5 parts sodium polyaspartate, 0.6 parts polyvinyl alcohol, 1.0 part nano-attapulgite, 1.2 parts zinc sulfate, 0.6 parts boric acid, 0.6 parts manganese sulfate, and 0.1 parts ammonium molybdate.

[0023] In this embodiment, the degree of polymerization of ammonium polyphosphate (APP) is 2~10, the degree of substitution of sodium carboxymethyl cellulose (CMC) is ≥0.9, the molecular weight of sodium polyaspartate (PASP) is 3000~8000, and the polyvinyl alcohol (PVA) is type 1788 with a degree of alcoholysis of 88%; the remaining raw materials are all conventional industrial products.

[0024] A method for producing a biopolymer-modified slurry graded crystallization water-soluble fertilizer includes the following steps: S1. Pretreatment of biopolymer modifier: Sodium carboxymethyl cellulose, sodium polyaspartate and polyvinyl alcohol are added to a high-speed mixer at a weight ratio of 3.5:1.5:0.6 and mixed at 900 rpm for 18 min to fully crosslink the three polymers and obtain a composite modifier; Nano-attapulgite is fed separately into an air jet mill and pulverized to D90≤2μm under 0.7MPa compressed air for later use; S2. Preparation of Crystallization Slurry: Add deionized water (1.2 times the total mass of solid raw materials) to a reactor equipped with a heating jacket and stirring device, heat to 88°C, and add ammonium polyphosphate, potassium nitrate, urea, and potassium sulfate in sequence, stirring at 180 rpm until completely dissolved to form a supersaturated slurry. The natural pH of the APP aqueous solution is 6.5, requiring no additional adjustment. S3. Simultaneous dispersion of nucleating agent and trace elements: The crushed nano-attapulgite clay, zinc sulfate, manganese sulfate, boric acid, and ammonium molybdate are added to a small amount of deionized water and ultrasonically dispersed for 18 minutes at 40 kHz and 200 W to form a stable suspension. The suspension is then slowly added to the crystallization slurry in step (2) and stirred for another 20 minutes. S4, High-temperature crystallization: S4.1, First-level high-temperature crystallization: The slurry containing nucleating agent and trace elements is cooled to 70℃ at 1.0℃ / min, and the composite modifier in step (1) is added (the amount added is 4.5% of the total mass of solid raw materials). The stirring speed is reduced to 90 rpm, and the mixture is stirred at a constant temperature for 30 min. APP-polymer composite crystals precipitate out and form fine crystal nuclei. S4.2 Secondary medium-temperature crystallization: The slurry after primary crystallization is cooled to 50℃ at a rate of 0.8℃ / min, the stirring speed is reduced to 70 rpm, and the crystallization is carried out at a constant temperature for 90 min, and the crystals grow into spherical aggregates; S4.3, Third-stage low-temperature aging: The slurry after secondary crystallization is cooled to 25℃ at 0.4℃ / min, the stirring speed is reduced to 40rpm, and it is aged for 150min to make the particle size distribution more uniform. S5. Graded filtration: A two-stage vibrating sieve-filtration system is adopted. The first stage filtration uses a 150-mesh sieve to retain crystals >0.1mm as coarse crystals and returns them to step (4) as seed crystals. The second stage filtration uses a 325-mesh sieve to retain crystals 0.045~0.1mm as finished crystals and enters the drying process. Fine crystals <0.045mm are returned to step (4) as seed crystals. S6. Mother liquor graded reuse: The first-level mother liquor (high temperature section) is directly returned to step (2) for batching, and the second-level mother liquor is returned to step (4) after evaporation and concentration. S7. Two-stage low-temperature drying: The finished crystals are fed into a fluidized bed dryer. The first stage involves processing with 48℃ hot air at a velocity of 1.8m / s for 25 minutes until the moisture content is ≤3%. The second stage involves processing with 32℃ hot air at a velocity of 1.2m / s for 12 minutes until the moisture content is ≤1.0%. S8. Screening and Packaging: Two-layer vibrating screens (0.3mm and 1.5mm) are used to collect qualified crystals of 0.3~1.5mm, which are then packaged in nitrogen-filled aluminum-plastic composite bags in an environment with a relative humidity of ≤25%.

[0025] Product performance: The fertilizer crystals prepared in this embodiment are spherical aggregates with a particle size of 0.3~1.5mm accounting for ≥90%, an agglomeration rate of ≤2.5%, a dissolution time of ≤80 seconds, and a cumulative phosphorus release rate of about 70% over 7 days, exhibiting excellent dual characteristics of rapid and slow release.

[0026] Example 2: A biopolymer modified slurry graded crystallization water-soluble fertilizer comprises the following raw materials in the indicated weight ratios: 32 parts ammonium polyphosphate, 22 parts potassium nitrate, 8 parts urea, 3 parts potassium sulfate, 2.5 parts sodium carboxymethyl cellulose, 1.0 part sodium polyaspartate, 0.4 parts polyvinyl alcohol, 0.6 parts nano-attapulgite, 0.8 parts zinc sulfate, 0.4 parts boric acid, 0.4 parts manganese sulfate, and 0.06 parts ammonium molybdate.

[0027] A method for producing a biopolymer-modified slurry graded crystallization water-soluble fertilizer includes the following steps: S1. Pretreatment with biopolymer modifier: CMC, PASP and PVA are mixed at a weight ratio of 2.5:1.0:0.4 and mixed at 800 rpm for 15 min. Nano-attapulgite is separately air-jet pulverized to D90≤2μm. S2. Preparation of crystallization slurry: The amount of deionized water is 1.0 times the total mass of solids. Heat to 82℃, add APP, potassium nitrate, urea and potassium sulfate in sequence, and stir at 150 rpm to dissolve. The natural pH is about 6.3. S3. Simultaneous dispersion of nucleating agent and trace elements: After ultrasonically dispersing nano-attapulgite with zinc sulfate, manganese sulfate, boric acid and ammonium molybdate for 15 minutes, add it to the slurry. S4, High-temperature crystallization: S4.1, First-stage high-temperature crystallization: Cool to 65℃ at 0.8℃ / min, add composite modifier (addition amount is 3.5% of the total solid mass), stir at 80 rpm, and keep at the temperature for 25 min; S4.2 Secondary medium-temperature crystallization: Cool to 45℃ at a rate of 0.6℃ / min, stir at 60 rpm, and crystallize at a constant temperature for 70 min; S4.3, Three-stage low-temperature aging: Cooling to 22℃ at 0.3℃ / min, stirring speed 35rpm, aging for 130min; S5. Hierarchical filtration: Same as in Example 1; S6. Mother liquor classification and reuse: Same as in Example 1; S7. Two-stage low-temperature drying: the first stage is treated with 45℃ hot air at a speed of 1.5m / s for 20 minutes; the second stage is treated with 30℃ hot air at a speed of 1.0m / s for 10 minutes.

[0028] S8. Screening and packaging: Same as in Example 1.

[0029] Product performance: The fertilizer crystals prepared in this embodiment are spherical aggregates with an agglomeration rate of ≤3.5% and a dissolution time of ≤100 seconds. All parameters of this scheme are in a low range, resulting in low production costs and making it suitable for large-scale industrial production with moderate product quality requirements.

[0030] Example 3: A biopolymer modified slurry graded crystallization water-soluble fertilizer comprises the following raw materials in the indicated weight ratios: 48 parts ammonium polyphosphate, 33 parts potassium nitrate, 14 parts urea, 8 parts potassium sulfate, 4.5 parts sodium carboxymethyl cellulose, 2.5 parts sodium polyaspartate, 0.7 parts polyvinyl alcohol, 1.4 parts nano-attapulgite, 1.8 parts zinc sulfate, 0.9 parts boric acid, 0.9 parts manganese sulfate, and 0.18 parts ammonium molybdate.

[0031] A method for producing a biopolymer-modified slurry graded crystallization water-soluble fertilizer includes the following steps: S1. Pretreatment with biopolymer modifier: CMC, PASP and PVA are mixed at a weight ratio of 4.5:2.5:0.7 and mixed at 1000 rpm for 20 min. Nano-attapulgite is separately air-jet pulverized to D90≤2μm. S2. Preparation of crystallization slurry: The amount of deionized water is 1.5 times the total mass of solids. Heat to 93℃, add APP, potassium nitrate, urea and potassium sulfate in sequence, and stir at 200 rpm to dissolve. The natural pH is about 6.8. S3. Simultaneous dispersion of nucleating agent and trace elements: After ultrasonically dispersing nano-attapulgite clay with zinc sulfate, manganese sulfate, boric acid and ammonium molybdate for 20 minutes, add it to the slurry. S4, High-temperature crystallization: S4.1, First-stage high-temperature crystallization: Cool to 75℃ at 1.2℃ / min, add composite modifier (addition amount is 5.5% of the total solid mass), stir at 100 rpm, and keep at the temperature for 40 min; S4.2, Secondary medium-temperature crystallization: Cool to 55℃ at a rate of 1.0℃ / min, stir at 80 rpm, and crystallize at a constant temperature for 110 min; S4.3, Three-stage low-temperature aging: Cooling to 28℃ at 0.5℃ / min, stirring speed 45rpm, aging for 170min; S5. Hierarchical filtration: Same as in Example 1; S6. Mother liquor classification and reuse: Same as in Example 1; S7. Two-stage low-temperature drying: the first stage is 50℃ hot air with a wind speed of 2.0m / s for 28 minutes; the second stage is 35℃ hot air with a wind speed of 1.4m / s for 14 minutes. S8. Screening and packaging: Same as in Example 1.

[0032] Product performance: The fertilizer prepared in this embodiment has the highest crystal sphericity, a clumping rate of ≤2.0%, a dissolution time of ≤70 seconds, a phosphorus cumulative release rate of about 65% over 7 days, and the best slow-release performance; this solution is suitable for high-end markets and long-distance storage and transportation scenarios.

[0033] The beneficial effects of this invention are: the crystal morphology is improved from the source, the physical properties of the product are significantly improved, and the fertilizer crystals prepared in the three embodiments are all spherical aggregates (the stability of the spherical morphology is also verified in Examples 2 and 3). This is in stark contrast to the needle-like or plate-like crystals obtained by the traditional crystallization method. The spherical particles have good fluidity and small contact area between particles, and are not easy to stick together during storage. The agglomeration rates of Examples 1-3 were controlled within 2.5%, 3.5% and 2.0% respectively, and further decreased with the improvement of modifier dosage and process control precision. Compared with traditional crystalline products in the industry (agglomeration rate is usually 8%~15%), the improvement is significant and the quality retention ability during storage is greatly enhanced. The dissolution times of the three examples were ≤80 seconds, ≤100 seconds, and ≤70 seconds, respectively, all of which were significantly better than the 90-120 seconds of traditional crystalline products. In particular, Example 3, through higher dosage of biopolymer modification and more refined crystallization control, further shortened the dissolution time to less than 70 seconds. This shows that the improvement in rapid dissolution is universal and reproducible, and can meet the basic requirements of water-soluble fertilizers for rapid solubility under different formulations and process parameters. Controllable particle size distribution and good batch consistency: All three examples achieved stable control of the target particle size of 0.3~1.5mm ≥90% through a three-stage crystallization process. The screening yield was high and the amount of return material was low, indicating that the graded crystallization strategy can maintain stable particle size control under different parameter combinations. The batch-to-batch product quality consistency is significantly better than that of traditional single-stage crystallization. The cumulative phosphorus release rates over 7 days in Examples 1-3 were approximately 70%, 75%, and 65%, respectively (based on the slow-release characteristics of APP itself, fluctuations under different parameters were controllable), all significantly lower than the rapid release (≥95%) of traditional orthophosphate fertilizers. This indicates that while changing the crystal morphology, the present invention fully retains the slow-release advantage of APP as a polymeric phosphorus source, giving the product both "fast-dissolving" and "slow-release" effects. Fast-dissolving refers to the physical properties during application, while slow-release refers to the nutrient release characteristics after application into the soil. The two are not mutually exclusive. Example 2, with a lower modifier dosage and relatively relaxed process parameters, still achieved basic performance of ≤3.5% agglomeration rate and ≤100 seconds dissolution time, at a lower cost. Example 3, using a higher dosage and more precise control, further reduced the agglomeration rate to within 2.0% and shortened the dissolution time to 70 seconds, resulting in better quality. This flexible adjustment capability from basic to high-end models demonstrates that product grades can be quickly switched according to market demand, possessing good industrial promotion value.

[0034] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A biopolymer-modified slurry graded crystallization water-soluble fertilizer, characterized in that, The raw materials include the following parts by weight: ammonium polyphosphate 30-50 parts, potassium nitrate 20-35 parts, urea 5-15 parts, potassium sulfate 0-10 parts, sodium carboxymethyl cellulose 2-5 parts, sodium polyaspartate 1-3 parts, polyvinyl alcohol 0.3-0.8 parts, nano-attapulgite 0.5-1.5 parts, zinc sulfate 0.5-2.0 parts, boric acid 0.3-1.0 parts, manganese sulfate 0.3-1.0 parts, and ammonium molybdate 0.05-0.2 parts; The fertilizer is a crystalline spherical aggregate with a composite modified layer of sodium carboxymethyl cellulose, sodium polyaspartate and polyvinyl alcohol embedded in the interior and surface of the crystal. Ammonium polyphosphate polymerizes phosphate and trace elements to form a chelate coordination structure.

2. The biopolymer-modified slurry graded crystallization water-soluble fertilizer according to claim 1, characterized in that, The sodium carboxymethyl cellulose has a degree of substitution ≥0.9, the sodium polyaspartate has a molecular weight of 3000~8000, and the polyvinyl alcohol is of type 1788 with a degree of alcoholysis of 88%; the weight ratio of sodium carboxymethyl cellulose, sodium polyaspartate and polyvinyl alcohol is 2~3:1:0.3~0.

5.

3. The biopolymer-modified slurry graded crystallization water-soluble fertilizer according to claim 1, characterized in that, The particle size D90 of the nano-attapulgite is ≤2μm, and the degree of polymerization of the ammonium polyphosphate is 2~10.

4. A method for producing a water-soluble fertilizer using a biopolymer-modified slurry with graded crystallization, characterized in that, Includes the following steps: S1. Pretreatment with biopolymer modifier: Sodium carboxymethyl cellulose, sodium polyaspartate and polyvinyl alcohol are added to a mixing device in a certain proportion and mixed evenly to obtain a composite modifier; nano-attapulgite is crushed separately to D90≤2μm using a crushing device. S2. Preparation of crystallization slurry: Add deionized water to the reactor, heat to 80~95℃, and add ammonium polyphosphate, potassium nitrate, urea and potassium sulfate in sequence, stirring to dissolve and form a supersaturated slurry; S3. Simultaneous dispersion of nucleating agent and trace elements: After dispersing nano-attapulgite with zinc sulfate, manganese sulfate, boric acid and ammonium molybdate, add it to the slurry and stir evenly; S4, High-temperature crystallization: S4.1, First-stage high-temperature crystallization: Cool the slurry to 65~75℃, add the composite modifier from step S1, stir for 20~40 minutes, and fine crystal nuclei will precipitate. S4.2, Secondary medium-temperature crystallization: Cool the slurry to 45~55℃, crystallize at a constant temperature for 60~120min, and grow crystals into spherical aggregates; S4.3, Three-stage low-temperature aging: Cool the slurry to 20~30℃ and age for 120~180min; S5. Staged filtration: After two stages of sieving and filtration, the crystals and mother liquor of each stage are collected separately. S6. Mother liquor reuse: Mother liquor from each stage is returned to the corresponding crystallization stage for recycling. S7. Low-temperature drying: Dry the collected crystals. The drying process is carried out at a temperature of 45~50℃ in the first stage and 30~35℃ in the second stage until the moisture content of the crystals is ≤1.0%. S8. Screening and Packaging: Collect the qualified crystals that have been dried in step S7 and have a size of 0.3~1.5mm, and package them in a moisture-proof manner to obtain the required water-soluble fertilizer.

5. The method for producing a biopolymer-modified slurry graded crystallization water-soluble fertilizer according to claim 4, characterized in that, In step S1, the weight ratio of sodium carboxymethyl cellulose, sodium polyaspartate, and polyvinyl alcohol in the composite modifier is 2~3:1:0.3~0.

5.

6. The method for producing a biopolymer-modified slurry graded crystallization water-soluble fertilizer according to claim 4, characterized in that, The amount of composite modifier added in step S1 is 3% to 6% of the total mass of solid raw materials, and the nano-attapulgite clay is pulverized by airflow to D90≤2μm.

7. The method for producing a biopolymer-modified slurry graded crystallization water-soluble fertilizer according to claim 4, characterized in that, The amount of deionized water used in step S2 is 1.0 to 1.5 times the total mass of the solid raw materials. In step S4, the pH value of the crystallization slurry does not need to be adjusted.

8. The method for producing a biopolymer-modified slurry graded crystallization water-soluble fertilizer according to claim 4, characterized in that, In step S3, the dispersion of nano-attapulgite soil and trace elements is carried out by ultrasonic dispersion equipment with ultrasonic vibration dispersion at a frequency of 40kHz, equipment power of 200W, and vibration dispersion time of 15~20min.

9. The method for producing a biopolymer-modified slurry graded crystallization water-soluble fertilizer according to claim 4, characterized in that, In step S5, the mesh sizes of the two-stage sieving and filtration are 150 mesh and 325 mesh, respectively. After the two-stage sieving and filtration, crystals with a particle size >0.1 mm are retained as coarse crystal fractions and returned to step S4 as seed crystals; crystals with a particle size of 0.045~0.1 mm are retained as finished crystals and enter the drying process in step S7; crystals with a particle size <0.045 mm are retained as fine crystal fractions and returned to step S4 as seed crystals.

10. The method for producing a biopolymer-modified slurry graded crystallization water-soluble fertilizer according to claim 4, characterized in that, In step S7, the first stage of the two-stage low-temperature drying has an air velocity of 1.5~2.0 m / s, and the second stage has an air velocity of 1.0~1.5 m / s; in step S8, the moisture-proof packaging uses an aluminum-plastic composite bag filled with nitrogen, and the relative humidity of the packaging environment is ≤25%.